(untitled) (Publicaciones en Ciencias y Tecnología, 2015)
This research was performed with the purpose of controlling the agents of physical hazards: noise, heat and lighting, in a Pipe Producing Company located in the Barquisimeto, Lara, Venezuela. The data were obtained from observations and unstructured and semi-structured interviews; in addition to that some studies of noise, heat and lighting were performed following the methodologies described in the COVENIN Venezuelan Standards 1565:1995, 2254:1995 and 2249:1993 respectively. It was determined that most workers are exposed to high levels of physical risks, because in some areas, the noise surpasses 85 dB (A), WBGT temperatures exceed 26,7 -C and lighting is under the 300 lux, showing breach of the valid regulations. For that reason it was proposed to encapsulate those points with more noise generation with an installation of extractors for heat control in addition to thermal insulation on the roof, and nally it was determined the need to install 168 lamps high pressure sodium both in the G1 and G2, at distances of 5 and 6 meters respectively.